38. FACTORS AFFECTING THE OUTCOMES OF SURGICAL TREATMENT WITH INTERNAL FIXATION USING LOCKING PLATE FOR THREE- TO FOUR-PART PROXIMAL HUMERUS FRACTURES IN OLDER ADULTS (Vietnam Journal of Community Medicine, 2024)
Background: Surgery for internal fixation using locking plate or shoulder arthroplasty remains a controversial issue in the treatment of complex 3-4 fragment fractures of the proximal humerus, especially in elderly patients. Despite the wider use of locking plate systems for the proximal humerus compared to head replacement, the complication rate after internal fixation with locking plates remains high. Risk factors such as low bone density, advanced age, loss of medial cortical support, and comminuted fractures can negatively impact treatment outcomes. The objective of this study is to evaluate the functional outcomes and imaging of the shoulder joint when using locking plates for the treatment of complex 3-4 fragment fractures of the proximal humerus in elderly patients, as well as the factors that may affect outcomes and complication rates at the Ho Chi Minh Hospital for Traumalogy and Orthopeadics. Method: A descriptive study was conducted on a series of cases involving 58 patients over 50 years old with 3-4 fragment proximal humerus fractures who underwent surgical correction combined with internal fixation using locking plate and screw at the Ho Chi Minh City Orthopedic Hospital. Result: 58 patients with a mean age of 62,78 ± 7,73 were followed up for an average of 26,24 ± 5,93 months after surgery. Among them, 41 cases had 3 fragment fractures, accounting for 70,68%, and 17 cases had 4 fragment fractures, accounting for 29,32%. At the final follow-up, the average Constant score for the patients was 70,81 ± 9,15, and the average DASH score was 8,33 ± 2,77. There were 6 cases of complications (10,34%). Among them, there was 1 case of avascular necrosis of the humeral head leading to screw penetration complication. The remaining cases included 1 cases of screw penetration, 3 cases of subacromial impingement, 1 case of avascular necrosis and 1 case of loss of reduction of greater tuberosity. The complexity of fractures, such as 4-fragment fractures, displacement greater than 2mm, and larger calcar fragment size resulted in lower Constant scores and higher DASH scores (p
Keywords: Proximal humerus fracture, open reduction internal fixation, osteoporosis, calcar margin.